Breast feeding, bottle feeding, and non-nutritive sucking; effects on occlusion in deciduous dentition. Issue 12 (19th November 2004) - Viggiano, D; Fasano, D; Monaco, G; Strohmenger, L
Abstract : Aims: To assess the effect of the type of feeding and non-nutritive sucking activity on occlusion in deciduous dentition. Methods: Retrospective study of 1130 preschool children (3–5 years of age) who had detailed infant feeding and non-nutritive sucking activity history collected by a structured questionnaire. They all had an oral examination by a dentist, blinded to different variables evaluated. Results: Non-nutritive sucking activity has a substantial effect on altered occlusion, while the effect of bottle feeding is less marked. The type of feeding did not have an effect on open bite, which was associated (89% of children with open bite) with non-nutritive sucking. Posterior cross-bite was more frequent in bottle fed children and in those with non-nutritive sucking activity. The percentage of cross-bite was lower in breast fed children with non-nutritive sucking activity (5%) than in bottle fed children with non-nutritive sucking activity (13%). Conclusions: Data show that non-nutritive sucking activity rather than the type of feeding in the first months of life is the main risk factor for development of altered occlusion and open bite in deciduous dentition. Children with non-nutritive sucking activity and being bottle fed had more than double the risk of posterior cross-bite. Breast feeding seems to have a protective effect on development of posterior cross-bite in deciduous dentition.